528 OUTCOMES IN DIABETIC PATIENTS WITH ACUTE MYOCARDIAL INFARCTION TREATED WITH SGLT2-I: THE SGLT2-I AMI PROTECT REGISTRY. (15th December 2022) - Paolisso, Pasquale; Bergamaschi, Luca; Gragnano, Felice; Gallinoro, Emanuele; Cesaro, Arturo; Sardu, Celestino; Mileva, Niya; Foà, Alberto; Armillotta, Matteo; Sansonetti, Angelo; Amicone, Sara; Impellizzeri, Andrea; et al.
Abstract: Background: Sodium-glucose co-transporter 2 inhibitors (SGLT2-I) receive intense clinical interest in patients with and without type 2 diabetes mellitus (T2DM) for their pleiotropic beneficial effects. Objectives: To investigate in-hospital and long-term prognosis in a cohort of T2DM patients presenting with acute myocardial infarction (AMI) treated with SGLT2-I versus other oral anti-diabetic (OAD) agents (non-SGLT2-I users). Methods: In this multicenter international registry all consecutive diabetic AMI patients undergoing percutaneous coronary intervention (PCI) between 2018 and 2021 were enrolled and, based on the admission anti-diabetic therapy, divided into SGLT-I users versus non-SGLT2-I users. In-hospital outcomes included cardiovascular death, recurrent AMI, occurrence of arrhythmias, and contrast-induced acute kidney injury (CI-AKI). Long-term outcomes were cardiovascular mortality, recurrent AMI, heart failure (HF) hospitalization, and their composite (MACE). Results: The study population consisted of 646 AMI patients (with or without ST-segment elevation): 111 SGLT2-I users and 535 non-SGLT-I users. The use of SGLT2-I was associated with a significantly lower in-hospital cardiovascular death, arrhythmic burden, and occurrence of CI-AKI (all p<0.05). During a median follow-up of 24±13 months, cardiovascular mortality, HF hospitalization and the composite endpoint were lower for SGLT2-I users compared to non-SGLT2-I patients (p<0.04 for all). After adjusting for confounding factors, the use of SGLT2-I was identified as independent predictor of HF hospitalization (HR=0.46; 95%CI:0.21-0.98; p=0.041) and MACE occurrence (HR=0.57; 95%CI:0.33-0.99; p=0.039). Conclusions: In T2DM AMI patients, the use of SGLT2-I was associated with a lower risk of adverse cardiovascular outcomes during index hospitalization and long-term follow-up. Our findings provide new insights into the cardioprotective effects of SGLT2-I in the setting of AMI.